Ways to Increase the Reading Speed of Younger Schoolchildren - Ashirbekova, A. B. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article raises the topic of reading speed of younger schoolchildren, and also considers ways to increase their reading speed.